The future of business : global issues in the 80's and 90's : published in cooperation with the Center for Strategic and International Studies, Georgetown University - Ways, Max, 1905-1985 (Pergamon policy studies., 1979)
The Future of Business: Global Issues in the 80s and 90s examines the future material, social, and intellectual vigor of business in the United States. The opportunities and problems facing business are analyzed, with emphasis on the basic forces and trends-both internal and external to business-that will largely shape it in the coming decades and their implications for society in general. This book is comprised of five chapters and begins with the argument that business corporations must be able to articulate a set of guiding principles that relate their conduct to the whole range of human a.